Analisis Determinan Perilaku Dissaving pada Generasi Muda - Izaty, Santi Nailul; Umairo, Tsania; Pratama, Versiandika Yudha (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
In the digital era, the financial patterns of the younger generation have undergone significant changes. Easy access to e-commerce platforms and digital financial services encourages the emergence of the dissaving phenomenon. This study aims to analyze the influence of financial education, consumption habits, and investment risk perceptions on the dissaving phenomenon among the younger generation. Using a quantitative approach, data were collected from 100 respondents aged 18–35 years in Pekalongan Regency through a questionnaire. The analysis was carried out using multiple linear regression with the help of SPSS 27. The results of the study showed that partially, financial education, consumption habits, and investment risk perceptions have a significant influence on dissaving. Simultaneously, the three variables explain 77.9% of the dissaving phenomenon. Financial education helps to manage the budget better, while uncontrolled consumption habits and high investment risk perceptions increase the risk of dissaving. This study highlights the importance of targeted financial education to suppress the dissaving phenomenon and proposes further research with a wider scope of variables and populations.